2019–2020 Florida Citrus Production Guide: Nutrition Management for Citrus Trees - Kelly T. Morgan; Davie M. Kadyampakeni; Mongi Zekri; Arnold W. Schumann; Tripti Vashisth; Thomas A. Obreza (EDIS)
The following description of citrus fertilizer uptake, soil and leaf testing and nutrient recommendations were taken from SL 253* and reflects citrus nutrient management for healthy trees prior to citrus greening or HLB entering Florida. Additional information on nutrients obtained since the publication was released appear in this document as "the effect of HLB" on various aspects of citrus nutrient management and are noted as such with published papers cited.